THE IDEAL CONCEPT OF ENERGY CONTROL IN INDONESIA FROM THE ECONOMIC CONSTITUTION PERSPECTIVE - Qurbani, Indah Dwi; Rafiqi, Ilham Dwi; Yofita, Emilda; Rahma, Nabila Aulia (Jurnal Pembaharuan Hukum, 2022)
Indonesia's energy transition trends are faced with many challenges and require support in several life sectors. Thus, the pledge of legal certainty and justice through the policies and legal arrangements has become a crucial factor. The present research employed normative legal research with a statutory, historical, and conceptual approach. The purpose of the research was to examine the regulation about energy control in Indonesia all this time and the prospects to regulate energy development from the economic constitution perspective. This study uses a normative juridical method with statutory, historical and conceptual approaches. The results had indicated that such a perspective became an ideal concept to be a basis, reference, and control to the energy regulation in the future. The economic constitution also implied that the economy was built as a shared effort referred to the principle of kinship. Consequently, each of the energy development elements, i.e., policy, management, regulation, and supervision had to be carefully measured for the sake of human’s prosperity. The development and use of renewable energy as the core energy source were strongly consistent with the actualization of economic welfare and safety among the people, which remarked the key to indicating the existence of the economic constitution.